Efeitos da produção e da sazonalidade sobre a qualidade do leite cru refrigerado processado em uma indústria de Minas Gerais - Claudio Antonio Versiani Paiva (2010)
In Brazil, the advance in the attainment of a quality raw material was intensified since 2005, when milk quality payment system was implanted by some industries of the sector, beyond the publication of Normative Instruction 51 by the Ministry of Agriculture that defined the microbiological and physical-chemical quality of bulk-cooled raw milk. The present study aimed to analyze the diverse variables that compose the status of the cooled raw milk quality, by evaluation of the data base of individual bulk milk tanks analyses, monthly computed from April 2002 to December 2008 at a dairy industry in Minas Gerais. The mean volume of milk in compliance with the IN51 for total bacterial count was 74.93% and 35.06% for the standard of years 2008 and 2011, respectively. For the somatic cells count, the mean volume of milk in compliance with the IN51 was 91.52% and 60.55% for the standard of years 2008 and 2011, respectively. In relation to the fat, protein, and solids nonfat, the mean volume of milk in compliance with the IN51 were 95.23%, 98.24%, and 89.63% for the standard of year 2008, respectively. The season variations affected the quality of the bulk-cooled raw milk. The determination of a selective collection of milk based on quality can be economically viable